Genome-wide identification and expression analysis of SPL with transmembrane motif (STM) transcription factor in Dendrobium officinale - Le YANG; Cong NIE; Xiaoqin LONG; Jize HE; Chaoyue YAN; Qiankun ZHU; Wanjun WANG (Guangxi Zhiwu, 2023)
SPL transcription factors are widely involved in plant growth and development, stress response and so on. At present, there is no study on the STM (SPL with transmembrane motif) transcription factor in Dendrobium officinale. In order to explore the role of STM in the growth, development and stress response of D. officinale, four STM transcription factors were identified at the whole genome of D. officinale, and bioinformatics analysis of DoSTM gene family members were carried out. The expression of DoSTM in different tissue parts and different stress treatments were studied by reverse transcription PCR. The results were as follows: (1)DoSTM1-4 were hydrophilic proteins with SBP conserved domains and some hormone response sites. (2)Four DoSTM were expressed in root, stem and leaf, and the relative expression of DoSTM2 was the lowest in leaf; there was no significant differences in the relative expression level of DoSTM1/3/4. (3)The relative expression level of DoSTM1-4 changed significantly under low temperature, high temperature and drought stress, and the expression of DoSTM1/3/4 decreased most significantly. Therefore, it is speculated that DoSTM is related to hormone response, temperature change response and drought resistance in plants. These conclusions provide the reference for the further research on STM transcription factor of D. officinale.